The time-dependent behaviour of anisotropic low density polyethylene - Clayton, David (Cranfield University, 1971)
'Low density polyethylene has been oriented into a state of transverse isotropy by cold-drawing an originally isotropic blank in uniaxial tension, and the non-linear creep behaviour of the material has been completely characterised for the first time. The compliance matrix describing the deformation behaviour is characterised by five independent material parameters. Four of the parameters have been determined from uniaxial tensile creep experiments on specimens cut at 0° and 90° to the draw direction, and the fifth from torsional creep studies on a specimen cut parallel to the draw direction. The- development and proof of experimental techniques for use with the respective apparatii have formed an important and necessary part of the work, and the accuracy and internal consistency of the results have been found to be excellent. Measurements of the compliances have been made at ten different: degrees of anisotropy - measured by the draw ratio - over a range of strains from the pseudo-linear to the highly nonlinear region. The anisotropy of the deformation behaviour at a given draw ratio, and the trends of anisotropy with draw ratio, have been interpreted in terns of current structural knowledge. At low draw ratios the deformation is dominated by a c-axis shear mechanism and an inter-lanellar shear mechanism, and a relaxation mechanism has been discovered in specimens cut at 90 to the draw direction. At high draw ratios an inter-fibrillar shear mechanism is dominant in specimens cut: at angles away from the 0° and 90° direction. A simple engineering analysis of the results has examined the applicability- of the formalisms of linear elasticity and viscoelasticity theory to the non-linear, anisotropic visco-elastic state. Also, the assumption of a constant volume deformation, which is commonly used in polymer science for the determination of the Poisson’s ratio terms, has been investigated over the range of strains and compared with directly measured values. The measured values represent the first systematic study of Poisson1s ratio in anisotropic polymers. The constant volume assumption is shown to be in error at all draw ratios.